Penguatan usaha kelompok budidaya ikan tawar “Mujur Fish Farm” dimasa pandemi Covid-19 dengan membangun mindset and spirit entrepreneur - Bahri Bahri; Widodo Prastyo; Dicky Dicky Arnendra Dwi Nugraha (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2021)
The rapid spread of Covid-19 in Indonesia led the government to impose physical distancing and Large-Scale Social Restrictions (PSBB) resulting in declining sales activity. One of the business groups affected by Covid-19 is the Fish Farming Group